Efficacy and Safety of Neoadjuvant Luteinizing Hormone-Releasing Hormone Antagonist and Tegafur-Uracil Chemohormonal Therapy for High-Risk Prostate Cancer - Fumiya Sugino; Keita Nakane; Makoto Kawase; Shota Ueda; Masayuki Tomioka; Yasumichi Takeuchi; Risa Tomioka-Inagawa; Toyohiro Yamada; Sanae Namiki; Naotaka Kumada; Shinichi Takeuchi; Kota Kawase; et al. (Life, 2023)
Background: This retrospective single-center cohort study evaluated the efficacy and safety of a combination of neoadjuvant luteinizing hormone-releasing hormone (LHRH) antagonist and tegafur-uracil (UFT) therapy (NCHT) and investigated the medical records of patients with high-risk PCa who underwent robot-assisted radical prostatectomy (RARP). The therapy was followed by RARP for high-risk PCa. Materials and Methods: The enrolled patients were divided into two groups: low-intermediate-risk PCa patients who underwent RARP without neoadjuvant therapy (non-high-risk) and those who underwent NCHT followed by RARP (high-risk group). This study enrolled 227 patients (126: non-high-risk and 101: high-risk group). Patients in the high-risk-group had high-grade cancer compared to those in the non-high-risk-group. Results: At the median follow-up period of 12.0 months, there were no PCa deaths; two patients (0.9%) died of other causes. Twenty patients developed biochemical recurrence (BCR); the median time until BCR was 9.9 months after surgery. The 2-year biochemical recurrence-free survival rates were 94.2% and 91.1% in the non-high-risk and high-risk-group, respectively (p = 0.465). Grade ≥3 NCHT-related adverse events developed in nine patients (8.9%). Conclusions: This study indicates that combining neoadjuvant LHRH antagonists and UFT followed by RARP may improve oncological outcomes in patients with high-risk PCa.